The Application of Semiotic Analysis in English Language Learning at Vocational High Schools for Health: A Case Study in a Small Class with 10 Students - Pratama Putriyani, Amanda (Universitas Muhammadiyah Enrekang, 2026)
This article aims to provide insight into the application of semiotic analysis in English language courses at a health vocational school using a case study of 10 students. The research focuses on the use of visual and verbal signs, such as instructional pictures, medical symbols, and English procedural texts, in teaching basic medical procedures, namely blood pressure measurement and IV drip insertion. This research uses a qualitative approach with a case study design. Data were collected through direct observation of learning activities, analysis of teaching materials, and interviews with students to explore their understanding and experiences in interpreting the learning material. The results show that images, symbols, and instructional texts function as effective semiotic signs in helping students understand complex medical procedures. These signs not only facilitate understanding of medical concepts and steps but also connect English learning with professional practice in the health sector. In addition, semiotic-based learning contributes to shaping students' professional identities as future health workers.